Serat Centhini Integration Builds Elementary Geographic Literacy: Integrasi Serat Centhini Membangun Literasi Geografi Siswa Sekolah Dasar - Pratiwi, Mey; Rachmadyanti, Putri; Puspita, Ari Metalin Ika (Academia Open, 2026)
General Background: Geographic literacy is a core competency in primary education encompassing spatial understanding, human–environment interaction, and cultural interpretation. Specific Background: Elementary Natural and Social Sciences learning in Indonesia often relies on textbooks and lacks contextual linkage to students’ real-world spatial experiences. Knowledge Gap: Previous studies have identified geographic values in Serat Centhini but have not deeply examined its integration process within classroom practice and learner experiences. Aims: This study investigates the integration of Serat Centhini as a culturally grounded source of geographic literacy in elementary IPAS learning. Results: Using a qualitative case study with 32 fifth-grade students and a teacher, findings show that narrative-based learning through Serat Centhini supports students’ understanding of spatial relationships, contextualizes geographic concepts, strengthens awareness of human–environment interactions, and connects cultural dimensions with geographic knowledge. Students demonstrated the ability to interpret spatial descriptions, relate them to real environments, and reflect on environmental values through culturally relevant narratives. Novelty: This study introduces a perspective that positions traditional Nusantara literature as an integrated pedagogical resource linking geographic literacy with cultural identity formation in elementary education. Implications: The findings highlight the potential of local literary heritage as an interdisciplinary and contextually meaningful learning resource, offering guidance for teachers, curriculum designers, and policymakers to incorporate culturally responsive approaches in geographic literacy development. Highlights• Narrative learning supports spatial concept comprehension through cultural storytelling• Students connect textual geography with real environmental contexts and practices• Cultural narratives foster ecological awareness and value-based reflection KeywordsGeographic Literacy; Serat Centhini; Local Wisdom; Narrative Learning; Elementary Education